HUBUNGAN POLA ASUH IBU DENGAN KEMAMPUAN TOILET TRAINING PADA ANAK USIA 12-24 BULAN DI PAUD BUAH HATI KAMPAR TAHUN 2018 - LANGEN NIDHANA MEYSIALLA; ALINI ALINI (Universitas Pahlawan Tuanku Tambusai, 2018)
Toilet training is an important aspect in the development of toddler age children, namely children aged 1 to 3 years where parents must pay more attention to defecation and urination. Learning toilet training in children is the first step in establishing children's independence. The purpose of this study was to determine the relationship of maternal parenting with toilet training abilities in children aged 12-24 months in Paud Buah Hati Kampar in 2018. This type of research was analytic with cross sectional design. The sample in this study were all mothers who had toddlers aged 12-24 months in Paud Buah Hati Kampar totaling 32 people, with the sampling technique carried out in total sampling. The data collection tool in this study uses a questionnaire. Analysis of the data used is univariate and bivariate analysis. The results showed that there was a relationship between maternal parenting and toilet training abilities in children aged 12-24 months at the age of the campar baby in 2018 with p value 0.013 <0.05. It is hoped that it can increase knowledge about toilet training and maternal attitudes and parenting in teaching toilet training practices to children.